Pedicle Dimensions of the Thoracic Vertebrae in the Zimbabwean Adult Male Population: A Cadaveric Study - Maimoona Khan, Takana Bill Nyamandi, Tapera Makosa, Maimoona Khan, Takana Bill Nyamandi, Tapera Makosa (Journal of Rawalpindi Medical College, 2022)
Objective: To record the dimensions of thoracic-vertebrae pedicles in the grown-up community of Zimbabwe. Study design: A cross-sectional descriptive study. Place and duration of study: A six-month study carried out in the Anatomy Department (Gross Anatomy Laboratory), University of Zimbabwe, College of Health Sciences, Harare (from May 2019 to November 2019). Material and Methods:. The thoracic vertebrae from 15 adult male cadavers were dissected out and Pedicle External Sagittal Diameter (PESD), Pedicle External Transverse Diameter (PETD) and chord length were measured using a vernier caliper and compared (on right and left sides). The statistical analysis was done using SPSS version 23, with data expressed as means, standard deviation and ranges. Student’s t-test was used to estimate the difference in pedicle dimensions of the right and left sides of the thoracic vertebrae. Results: There was a significant difference between the right and left pedicle dimensions in chord length at the level of T9, PESD at levels T6 and T7, and PETD at levels T2, T6, T7 and T11. PESD values were noted to be increasing from thoracic vertebrae T1 to T12 with a plateau phase noted from T2-T7. PETD values decreased from T1-T5 and then gradually increased to T12. Chord length increased gradually from T1-T12. Conclusion: Pedicle dimensions differ between the Zimbabwean population and other ethnic groups of earlier investigations. Furthermore, there was a significant difference between the right and left pedicles in terms of PETD, PESD and Chord length.